1991
DOI: 10.1007/bf01288197
|View full text |Cite
|
Sign up to set email alerts
|

Fission following complete or incomplete fusion of 135 MeV16O and238U

Abstract: From measurements of the laboratory angular distribution and the projected range distribution for each of 26 individual radioactive fission products from the interaction of 135 MeV 160 on 23sU, we have determined for each product quantities including the average velocity, v, of the parent fissioning system and the anisotropy, co, of the fission angular distribution. We have interpreted the results in terms of two competing mechanisms: complete fusion and a process involving transfer of an e-particle from proje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Recently Parker et al [2,3] carried out similar studies on 16 0-induced fission of 238 U at 101 and 135 MeV. The results on 12 C-induced fission of 232 Th were reported by Manohar et al [4], These investigations have been useful in the understanding of the nature of the reaction by comparison of the mass distribution with that observed in the low energy fission, as well as in alpha particle and proton induced fission of actinides.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Recently Parker et al [2,3] carried out similar studies on 16 0-induced fission of 238 U at 101 and 135 MeV. The results on 12 C-induced fission of 232 Th were reported by Manohar et al [4], These investigations have been useful in the understanding of the nature of the reaction by comparison of the mass distribution with that observed in the low energy fission, as well as in alpha particle and proton induced fission of actinides.…”
Section: Introductionmentioning
confidence: 61%
“…The beam current on the target was measured by an electron-suppressed Faraday cup and was in the range of 10 to 15 nA (particle). After irradiation, the target along with the catcher was counted for fission product activities using an efficiency-calibrated 60 cm 3 HPGe detector coupled to a PC based 4 k MCA. The resolution of the detector was 1.8 keV at 1332 keV.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, the fission reaction for the ' 0+ U system has been investigated at E&,b =101 and 135 MeV by means of a catcher technique providing other interesting information for the fission fragment properties such as their velocity and mass distributions [3,4]. It was confirmed that at the lowest energy (101 MeV) peripheral interactions contribute within a few percent to the total fission reaction cross section, whereas at the incident energy of 135 MeV a large fraction of the cross section, about 24%, has been interpreted as due to the fusion of an a particle with the target nucleus.…”
Section: Introductionmentioning
confidence: 99%
“…Although this is not a surprising result, it must be viewed in the light of the extensive work on fission fragment angular correlations of Viola and co-workers [5,20,21], which seems to indicate that the fission channel is populated mainly by cornpete fusion and single alpha transfer, an approach we ourselves have been successful with in fission studies [13,14]. It remains unclear why spallation stems from, in addition to complete fusion, cz and Be transfer with the latter more important, while fission channels seem to tap principally the complete fusion and alpha transfer channels.…”
Section: Introductionmentioning
confidence: 80%